Reticulate leaves and stunted roots are independent phenotypes pointing at opposite roles of the phosphoenolpyruvate/phosphate translocator defective in cue1 in the plastids of both organs - Staehr, Pia; Löttgert, Tanja; Christmann, Alexander; Krueger, Stephan; Rosar, Christian; Rolčík, Jakub; Novák, Ondřej; Strnad, Miroslav; Bell, Kirsten; Weber, Andreas P. M.; Flügge, Ulf-Ingo; Häusler, Rainer E. (Frontiers in Plant Science, 2014)
Phosphoenolpyruvate (PEP) serves not only as a high energy carbon compound in glycolysis, but it acts also as precursor for plastidial anabolic sequences like the shikimate pathway, which produces aromatic amino acids (AAA) and subsequently secondary plant products. After conversion to pyruvate, PEP can also enter de novo fatty acid biosynthesis, the synthesis of branched-chain amino acids, and the non-mevalonate way of isoprenoid production. As PEP cannot be generated by glycolysis in chloroplasts and a variety of non-green plastids, it has to be imported from the cytosol by a phosphate translocator (PT) specific for PEP (PPT). A loss of function of PPT1 in Arabidopsis thaliana results in the chlorophyll a/b binding protein underexpressed1 (cue1) mutant, which is characterised by reticulate leaves and stunted roots. Here we dissect the shoot- and root phenotypes, and also address the question whether or not long distance signalling by metabolites is involved in the perturbed mesophyll development of cue1. Reverse grafting experiments showed that the shoot- and root phenotypes develop independently from each other, ruling out long distance metabolite signalling. The leaf phenotype could be transiently modified even in mature leaves, e.g. by an inducible PPT1RNAi approach or by feeding aromatic amino acids (AAA), the cytokinin trans-zeatin (tZ), or the putative signalling molecule dehydrodiconiferyl alcohol glucoside (DCG). Hormones, such as auxins, abscisic acid, gibberellic acid, ethylene, methyl jasmonate, and salicylic acid did not rescue the cue1 leaf phenotype. The low cell density1 (lcd1) mutant shares the reticulate leaf-, but not the stunted root phenotype with cue1. It could neither be rescued by AAA nor by tZ. In contrast, tZ and AAA further inhibited root growth both in cue1 and wild-type plants. Based on our results, we propose a model that PPT1 acts as a net importer of PEP into chloroplast, but as an overflow valve and hence exporter in root plastids.